1993
DOI: 10.1002/1097-0142(19931101)72:9<2568::aid-cncr2820720910>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma resembling hodgkin disease after posttransplant lymphoproliferative disorder in a liver transplant recipient

Abstract: Background. Posttransplant Epstein‐Barr virus (EBV)‐associated lymphoproliferative disorders (PTLD) are B‐cell derived tumors of polymorphic to monomorphic histologic type. Hodgkin disease (HD) is not considered part of this spectrum and rarely occurs in the posttransplant population. A liver allograft recipient is reported who had a PTLD develop that resolved after a reduction of immunosuppression. Several years later, the patient had a separate lymphoid tumor develop that resembled HD. The relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…The case of patient 2 illustrates the possible transformation of a monoclonal B cell lymphoproliferation into a monoclonal NHL. This pattern has already been described in a patient treated with cyclosporin A (15). The kinetic studies reported here stress the need for a cautious followup of such patients.…”
Section: Discussionsupporting
confidence: 82%
“…The case of patient 2 illustrates the possible transformation of a monoclonal B cell lymphoproliferation into a monoclonal NHL. This pattern has already been described in a patient treated with cyclosporin A (15). The kinetic studies reported here stress the need for a cautious followup of such patients.…”
Section: Discussionsupporting
confidence: 82%
“…Although this study included most of the pathologic subtypes of PTLD previously described by Nalesnik et al [22][23][24], Frizzera et al [25], Knowles et al [26] and summarized by Swerdlow [27], including EBV negative forms [18], the small number of cases did not permit an analysis of the relationship between histology and prognosis. Other factors that have shown prognostic significance in immune competent or compromised patients with lymphoma include age, sex, stage, serum LDH, the presence of extranodal disease or presentation with B symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Late-presenting PTLD tends to behave much like a true lymphoma, is frequently difficult to control, and has greater mortality. Hodgkin's lymphoma, T-cell lymphoma, Burkitt's lymphoma, and non-Hodgkin's lymphoma have been described 91 and, in many instances, are associated with the EBV virus.…”
Section: Monitoring For Long-term Complications Of Immunosuppressionmentioning
confidence: 99%